Contribution of food groups to sodium and potassium intakes by their ratio in Korean adults - Choi, Mi-Kyeong; Kim, Nam-Young; Lee, Yeon-Kyung; Heo, Young-Ran; Hyun, Taisun; Oh, Se-Young; Park, Hyeryun; Ro, Hee-Kyong; Lyu, Eun-Soon (Progress in Nutrition, 2019)
Background/Aims: Koreans have relatively high sodium intakes, and a higher sodium-to-potassium (Na/K) ratio is associated with increased mortality resulting from cardiovascular diseases. The purpose of this study was to analyze the dietary patterns and food groups that contribute to sodium and potassium intakes according to dietary Na/K ratio in Koreans. Methods: A 24-hour dietary recall was collected twice from 640 healthy adults (aged 19-69 years) in four Korean provinces. The subjects were divided into groups of Na/K<1 and Na/K≥1, and their dietary pattern focused on sodium and potassium intakes and Na/K ratio of major food groups were analyzed and compared. Results: The average Na/K ratio of the subjects was 1.5; the highest ratio was in the twenties. Daily sodium and potassium intakes were significantly high in the Na/K≥1 group and the Na/K<1 group, respectively. Sodium intake from grains, meat, fish, and seasonings of the Na/K≥1 group and potassium intake from potatoes, beans, nuts, and fruits of the Na/K<1 group were significantly higher than the counterpart groups. Food groups with the lowest Na/K (0.1) were fruits, cooked rice, and beans, and a Na/K ratio greater than 10.0 included seasonings and salted seafood. The Na/K<1 group consumed more fruits and potatoes and the Na/K≥1 group consumed more grains, beverages, meats, and seasonings. Conclusions: Dietary Na/K ratio of Koreans was significantly higher than Korean or WHO guidelines. Recommendation of reducing sodium intake from grains, meats, and seasonings and increasing potassium intake from fruits, potatoes, and beans may be suggested for lowering the Na/K ratio.